Assessing Mbiotisho: A smartphone application used to collect high‐frequency health and nutrition data from difficult‐to‐reach populations - Jensen, Nathaniel D.; Lepariyo, Watson; Alulu, Vincent; Sibanda, S.; Kiage, B.N. (Wiley, 2023)
There is an urgent need for improved and timely health and nutrition data. We developed and tested a smartphone application that caregivers from a pastoral population used to measure, record and submit high‐frequency and longitudinal health and nutrition information on themselves and their children. The data were assessed by comparing caregiver‐submitted measurements of mid–upper arm circumference (MUAC) to several benchmark data sets, including data collected by community health volunteers from the participating caregivers during the project period and data generated by interpreting photographs of MUAC measurements submitted by all participants. We found that the caregivers participated frequently and consistently over the 12‐month period of the project; most of them made several measurements and submissions in at least 48 of the 52 weeks of the project. The evaluation of data quality was sensitive to which data set was used as the benchmark, but the results indicate that the errors in the caregivers' submissions were similar to that of enumerators in other studies. We then compare the costs of this alternative approach to data collection through more conventional methods, concluding that conventional methods can be more cost‐effective for large socioeconomic surveys that value the breadth of the survey over the frequency of data, while the alternative we tested is favoured for those with objectives that are better met by high‐frequency observations of a smaller number of well‐defined outcomes.